2006
DOI: 10.1002/eji.200535244
|View full text |Cite
|
Sign up to set email alerts
|

Impaired regulatory T cell function in germ‐free mice

Abstract: Regulatory T cells (Treg) are crucial for the maintenance of tolerance to auto-antigens and harmless exogenous antigens. Here, we studied the role of the commensal microbiota for the development and function of Treg. CD4 + CD25 + T cells were obtained from peripheral lymph nodes (PLN) and mesenteric lymph nodes (MLN) of germ-free (GF) and conventional (conv) NMRI mice and tested for phenotype and functional suppressive capacity. CD4 + CD25 + T cells from GF mice showed a lower relative gene expression of fork … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(172 citation statements)
references
References 59 publications
8
156
1
3
Order By: Relevance
“…The fetal intestine is sterile at birth, but colonization by a variety of microorganisms begins directly after delivery (31). Because murine studies show that exposure to bacterial Ags favor the generation and/or expansion of functional Treg it is likely that acquisition of commensal flora is necessary to kick-start the tolerogenic mechanisms in of the immune system (32)(33)(34). In addition, Treg from germfree mice are less suppressive than those from conventional or colonized but pathogen-free mice, and they also express less FOXP3 than conventional mice (33,34).…”
Section: Foxp3mentioning
confidence: 99%
“…The fetal intestine is sterile at birth, but colonization by a variety of microorganisms begins directly after delivery (31). Because murine studies show that exposure to bacterial Ags favor the generation and/or expansion of functional Treg it is likely that acquisition of commensal flora is necessary to kick-start the tolerogenic mechanisms in of the immune system (32)(33)(34). In addition, Treg from germfree mice are less suppressive than those from conventional or colonized but pathogen-free mice, and they also express less FOXP3 than conventional mice (33,34).…”
Section: Foxp3mentioning
confidence: 99%
“…Natural thymic-dependent Treg (CD4 1 CD25 hi FoxP3 1 ) are fundamental in protection against autoimmunity, gut inflammation and IgE responses. This cell subset has reduced functional capacity in germ-free animals [8].…”
Section: Introductionmentioning
confidence: 99%
“…Natural thymic-dependent Treg (CD4 1 CD25 hi FoxP3 1 ) are fundamental in protection against autoimmunity, gut inflammation and IgE responses. This cell subset has reduced functional capacity in germ-free animals [8].The strongest T-cell activators known are the ''superantigens'', exotoxins produced by certain pathogenic bacteria such as Staphylococcus aureus. These include staphylococcal enterotoxin A, B, C, D and E, as well as toxic shock syndrome toxin-1.…”
mentioning
confidence: 99%
“…It has been previously shown that the number of T cells remarkably decreases in germ-free mice (mice without intestinal microbiota), suggesting that T cells accumulate following recruitment by bacterial materials (23)(24)(25). The specificity of these cells is not known at present, although it seems that many of them are probably exclusive to commensal microbiota and the products to prevent damage caused by pathogens or toxins (22).…”
Section: T Cells and Microbiota In The Colonmentioning
confidence: 99%